Assessing the Market Power of Digital Platforms - Tiago S. Prado (International Telecommunications Society (ITS), 2021)
In this conceptual paper, I propose a framework for measuring the market power of digital platforms. The rise of big technology companies that act both as intermediary platforms and providers of services and goods in several markets has heightened concerns about potential economic harms brought by the concentrated structure of the digital economy. However, the operationalization of market power in the platform economy and the procedures to define which digital platforms and markets should be targeted by pro-competitive remedies, either under a competition policy framework or under a regulatory regime, remain highly contested. I demonstrate that large technology platforms can leverage their market power across markets in the digital economy to make their end users unlikely to switch to smaller competitors, even when they offer better services. Based on this analysis, I argue that market-specific approaches, such as the commonly used Significant Market Power (SMP) framework, would have limited impact in promoting competition in digital markets. I then propose a new set of tools aimed to identify the market power of digital platforms in two-sided markets and suggest some policy alternatives to harness the potential of pro-competitive remedies in the digital economy.
Keywords: L12; L13; L41; L44; L51; 330; digital platform; digital economy; market power; competition policy; regulation